Rola komunikacji przedsiębiorstwa z otoczeniem w kreowaniu wizerunku firmy - Gromala, Patrycja (My University, 2011)
Celem niniejszej pracy magisterskiej było ukazanie roli komunikacji z otoczeniem w kreowaniu wizerunku firmy. Na przebieg pracy składały się następujące etapy: 1. Część teoretyczna – opis kluczowych zagadnień. 2. Cześć empiryczna - opis populacji badawczej - opis metod badawczych - ankieta - wyniki i ich interpretacja względem postawionych hipotez Przeprowadzone badania wykazały, że komunikacja ma duże znaczenie dla przedsiębiorstw wraz z ich otoczeniem. Pomaga także wzmacniać i kreować wizerunek firmy.

The purpose of present Thesis was to show the role of business communication with the environment in creating the company’s image. Thesis consisted of the following stages: 1. Theoretical part - description of the key issues. 2. Research part - Description of the research population - Description of the research methods - Questionnaire form - Results and interpretation Results of the thesis have shown that communication it is important for businesses and their surroundings. Also helps to strengthen and create brand image.
Business communication with the environment in creating the company's image
Keywords: komunikowanie; wizerunek; otoczenie przedsiębiorstwa; ankieta; communication; image; environment; questionnaire form